2021
DOI: 10.1007/s11218-021-09636-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of passion for studies on academic procrastination and mental health during the COVID-19 pandemic

Abstract: Procrastination is a maladaptive behaviour that students often experience in academic activities and can result in negative consequences to mental health. The challenges imposed by the COVID-19 pandemic can contribute to increase procrastination behaviors in academic activities that the student does not like and in those he/she is passionate. The main objective of this research was to test an integrative model of passion, procrastination, satisfaction with life and psychological distress in students during pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 46 publications
4
49
0
8
Order By: Relevance
“…In addition, other studies also explain the reasons or causes of academic procrastination, including not being confident in their abilities (Wulandari et al, 2021). In addition, anxiety or worry about students' self-obsessive desires may not meet self-standards or expectations (Peixoto et al, 2021). This research contributes to universities providing treatment so that academic dishonesty behavior does not continue in students.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, other studies also explain the reasons or causes of academic procrastination, including not being confident in their abilities (Wulandari et al, 2021). In addition, anxiety or worry about students' self-obsessive desires may not meet self-standards or expectations (Peixoto et al, 2021). This research contributes to universities providing treatment so that academic dishonesty behavior does not continue in students.…”
Section: Resultsmentioning
confidence: 98%
“…Previous research has reported that academic procrastination is related to personality, namely in aspects of low awareness (competence, orderliness, devotion, struggle for achievement, self-discipline, deliberation) and aspects of neuroticism (anxiety, depression, self-awareness, impulsivity, vulnerability) (Watson, 2001). Recent research has also suggested that procrastination is caused by personality extraversion and neuroticism (Kim et al, 2017), is negatively associated with harmonious desires, and positively associated with obsessive desires (Peixoto et al, 2021). they are influencing self-efficacy.…”
mentioning
confidence: 99%
“…For example, Tice and Baumeister (1997) demonstrated that procrastinators’ stress levels increase substantially over the course of a semester, whereas those of nonprocrastinators do not. A study conducted during the COVID-19 pandemic (Peixoto et al, 2021, N = 416) showed that greater academic procrastination predicted greater psychological distress (e.g., stress, depression, anxiety; r = .34) and lower life satisfaction ( r = –.37) among university students.…”
Section: What Is Known About Procrastinationmentioning
confidence: 99%
“…Academic procrastination is a phenomenon whereby an individual intentionally delays some learning tasks that must be completed without regard for the possible adverse consequences. The challenges posed by the COVID-19 pandemic can increase procrastination in academic activities that a student either dislikes or is passionate about (Peixoto et al, 2021). The relationship between the two phenomena deserves more in-depth study.…”
Section: Introductionmentioning
confidence: 99%